Identifying the Factors That Hinder Sustainable Dietary Modification and Successful Weight Loss in Obese Adult - Alfouzan, Nouf (Curr Dev Nutr, 2020)
OBJECTIVES: The Individualized Diet Improvement Program (iDip) is a year-long, group session-based weight loss program to help participants experiment and discover a sustainable dietary modification. We observed a large difference among participants in weight loss success. The objective is to identify factors that explain the difference in weight loss magnitude among participants. METHODS: 30 participants (25–70y) enrolled in an ongoing iDip study. A self-reflection survey was designed and administrated at eight months to determine the factors that could account for the differential weight loss outcome. The survey consisted of 19 dietary implementation statements and 19 behavior change statements. A degree of dietary implementation was scored from 0 (Have not tried) to 3 (Well implemented). Difficulty in a behavior change was scored from 0 (Strongly agree) to 4 (Strongly disagree). The survey scores were compared between top and bottom tertile groups in weight loss success. Two-tailed t-test was used for statistical analysis. RESULTS: 21 out of 24 remaining participants returned the survey. Mean weight loss of the top, middle, and bottom tertiles (n = 7 each) was −14.8 ± 2.9, −5.2 ± 0.6 and −1.3 ± 0.6 kg (mean ± SEM) at eight months, respectively. The sum of dietary implementation statement scores in the bottom tertile group (14.5 ± 1.2) was significantly lower (P < 0.05) than that of the top tertile group (17.7 ± 1.1). The score of the bottom tertile group was also significantly lower than that of the top tertile group in the following statements: exchanging protein sources for leaner options (2.00 vs.2.86), selecting higher protein and fiber density foods (1.71 vs. 2.43), making meals high in protein and fiber (1.57 vs. 2.29), and finding staple food high in protein and fiber (1.86 vs.2.57). No difference was observed in the sum of behavioral statement scores between the two groups. Only one statement, “it is demotivating when seeing others losing weight”, was found significant among individual behavioral statements (bottom and top tertile groups, 3.1 and 3.7, respectively. CONCLUSIONS: The survey indicates that the main obstacles to successful weight loss are difficulty in establishing meal routine and selecting foods high in protein and fiber per energy. In addition, lack of success in weight loss is likely to decrease motivation. FUNDING SOURCES: USDA NIFA; NIBIB NIH (CA).